Ecological Analysis of Community and Private Partnership in Tree Planting Program to Rehabilitate Degraded Lands: A Case Study in East Java, Indonesia - Hapsari, Lia; Yulistyarini, Titut; Trimanto; Danarto, Setyawan Agung; Mas'udah, Shofiyatul; Damaiyani, Janis; Laksono, Rachmawan Adi; Jati, Ardiawan; Budiharta, Sugeng (Jurnal Manajemen Hutan Tropika, 2023)
Community and private partnership (CPP) in tree planting initiative is potential to accelerate rehabilitation of degraded lands. Yet, empirical studies to analyse such programs are limited. Here, we analysed a CPP tree planting program in East Java, Indonesia by focusing on ecological aspects, i.e. vegetation cover changes, floristic diversity, above-ground carbon storage, and soil and microclimate conditions. Results showed that there was a striking increase in vegetation cover, yielding a total carbon sequestration of 3,853 tons, or equivalent to the reduction of 14,140 tons of CO2 emissions. On the other hand, co-benefits in term of floristic diversity at a landscape scale was low, and soil and micro-climate conditions were still marginal. This study provided empirical evidence that collaboration between communities and private entities in tree planting program can be effective in rehabilitation of degraded lands. Improvement in land management systems applied in tree planting through the implementation of mixed gardens or complex agroforestry is suggested if aiming for co-benefits in floristic diversity and soil properties. Our study recommends a broader adoption of a similar scheme in rehabilitation of degraded lands across Indonesia.